The Impact of Small Games Proposed Program on Development of Emotional Intelligence in Summer Camps Children (9-11) Years Old - Kouadri Rana; Abdelli Fateh (My University, 2022)
THE OBJECT OF THE STUDY AIMS TO IDENTIFY THE IMPACT OF A PROPOSED PROGRAM BASED ON SMALL GAMES IN THE DEVELOPMENT OF THE EMOTIONAL INTELLIGENCE IN SUMMER CAMPS CHILDREN (9-11) YEARS OLD, FOR THIS PURPOSE, WE USED THE METHOD OF AN EXPERIMENTAL APPROACH WITH AN EXPERIMENTAL DESIGN WHICH CONTAINS TWO GROUPS OF INDIVIDUALS, ON A SAMPLE COMPOSED OF 30 CHILD FROM KARMA CAMP BOUMERDESS. CHOSEN AS AN EXPERIMENTAL GROUP (15 CHILD) AND A CONTROL GROUP (15 CHILD), AND FOR DATA COLLECTION, WE USED A TOOL OF ACTIVATOR OBSERVATION FORM OF DANIAL GOLEMAN’S EMOTIONAL INTELLIGENCE SCALE AFTER COLLECTING THE RESULTS AND HAVING TREATED THEM STATISTICALLY, WE CONCLUDE THAT THE PROPOSED PROGRAM BASED ON SMALL GAMES HAS AN IMPACT IN DEVELOPING EMOTIONAL INTELLIGENCE IN THE CAMP'S CHILDREN. ON THIS BASIS, THE STUDY RECOMMENDED TO INTRODUCE THE PROPOSED SMALL GAMES PROGRAM IN CAMPS AND TRAINING, TAKING ACCOUNT THE DEVELOPMENT OF CHILDREN'S EMOTIONAL INTELLIGENCE.